Lusus naturae:climate and invasions of plant pathogens modify agricultural and forest lands - Salvatore Moricca; Alessandro Ragazzi (Italian Journal of Agronomy)
The ecological and economic sustainability of agricultural and forest systems of many advanced and underdeveloped Countries are strongly threatened by the increasing introduction of exotic plant pathogens. This article provides an overview of the main causes behind these invasions. Some important diseases caused by non native phytopathogens, whose arrival in the past century had a disastrous impact on the environment and economy of vast rural areas of our Country are reported. Some dangerous, emerging pathogens, which are literally destroying whole territories in various parts of the Planet, with severe damage to agricultural crops, landscape, economy and local tourism are also reported. Action strategies to prevent immigration of unwanted pathogens, and mitigation strategies, aimed at the development of various measures to mitigate the negative effects of plant parasites already established in the territory are then discussed. Finally, it is highlighted how such a far-reaching problem can be properly tackled only with the active contribution of governments, institutions responsible for plant health monitoring (warning services), research, and agricultural, tourism and transport operators.